2006
DOI: 10.1159/000093968
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of the Human Fetal Kidney Size

Abstract: Early prenatal diagnostics and the importance of genetic counseling are of great interest for echosonographic evaluation of normal fetus anatomy. Development of the human fetal kidney runs through a series of continual and mutually dependent changes during which the kidney obtains its morphological and functional maturity. This study was created to estimate the changes in kidney size during gestation in fetuses from the 4th to the 10th lunar month, to evaluate the dynamics of their growth, as well as to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Our charts of the fetal kidney and fetal renal pelvis were derived from longitudinal data obtained from prospective investigations that were carried out specifically for the development of centile charts for assessing renal size at a known gestational age between 16 and 42 weeks of gestation. Several charts of fetal kidney size have been published, but a number of the previous studies had shortcomings in their data collection or suffered from methodological pitfalls and used incorrect methods in their design. Moreover, our study has the added advantage that the statistical analysis used is able to correct for missing data.…”
Section: Discussionmentioning
confidence: 99%
“…Our charts of the fetal kidney and fetal renal pelvis were derived from longitudinal data obtained from prospective investigations that were carried out specifically for the development of centile charts for assessing renal size at a known gestational age between 16 and 42 weeks of gestation. Several charts of fetal kidney size have been published, but a number of the previous studies had shortcomings in their data collection or suffered from methodological pitfalls and used incorrect methods in their design. Moreover, our study has the added advantage that the statistical analysis used is able to correct for missing data.…”
Section: Discussionmentioning
confidence: 99%
“…Most accurate method is by three dimensional ultrasound with VOCAL method and most widely acceptable. (18,19) However doing three-dimensional ultrasound for kidney volume is not cost effective and hence we preferred doing two dimensional ultrasound in our study to calculate fetal renal volume which was more feasible and more or less precise.…”
Section: Correlations(iugr)mentioning
confidence: 99%
“…(20) However others did not agree as they considered that kidney is not true ellipsoid and found that 24% to 32% underestimation of the fetal renal volume while using two dimensional ultrasound. (18,21) Renal Doppler parameters which we included in our study were peak systolic velocity, end diastolic velocity and pulsatility index. Renal artery pulsatility index is a measure of renal artery resistance and hence renal blood flow.…”
Section: Correlations(iugr)mentioning
confidence: 99%
“…We adjusted the renal pelvic diameter and renal volume with the fetal head circumference because the gestational age at sonography varied among the patients in this study (range, 30–39 weeks). We wanted to eliminate unnecessary bias according to fetal sizes and gestational ages 32 , 33 . Usually, the abdominal circumference is considered the parameter most strongly correlated with fetal sizes rather than other parameters 34 – 36 .…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to eliminate unnecessary bias according to fetal sizes and gestational ages. 32,33 Usually, the abdominal circumference is considered the parameter most strongly correlated with fetal sizes rather than other parameters. [34][35][36] However, we chose to use the head circumference, a bony structure, because the abdominal circumference can be affected by hydronephrotic conditions in fetuses.…”
Section: Discussionmentioning
confidence: 99%